STEM-professional women's exclusion in the Canadian space industry : anchor points and intersectionality at the margins of space - Ruel, Stefanie (Critical management studies (Series), 2019)
STEM-Professional Women's Exclusion in the Canadian Space Industry: Anchor Points and Intersectionality at the Margins of Space showcases the how' of exclusion of STEM-professional women from management and executive positions. It examines the discourses and power-relations surrounding these STEM-professional women's identities, drawing on and reworking the concept of anchor points to investigate their relationship to structural, discursive, and socio-psychological processes. By utilizing the critical sensemaking (CSM) framework, the book provides an avenue to surface the ephemeral identities of STEM-professional women, and investigate their relationship with the meta-rules, rules, and social values of the Canadian space industry. It also considers the potential for social change across this industry by considering the responsibilities of cisgender men with respect to addressing and resisting the systemic discrimination of STEM-professional women in the industry. Specific sites for micro-political resistances that these STEM-professional women could enact are considered and suggested. This book will appeal to researchers and scholars focused on gender and diversity, intersectionality scholarship, and poststructuralist intersectional feminism.